The Role of ESG (Environmental, Social, Governance) on Dividends and Firm Value: The Moderation Effect of Audit Quality - Clarissa Dominique Effendi Handajani; Werner R. Murhadi (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
This research will examine the influence of ESG (Environmental, Social, Governance) and its components on dividends and firm value. Furthermore, the quality and credibility of information in the market will also influence stakeholder assessments. The important role of audit quality in providing assurance on this information is needed. By using multiple linear regression on 252 firm years from companies listed in IDX 2020-2023 that meet the sample criteria, it was found that ESG has not been able to significantly influence dividends and firm value. However, environmental can influence dividends in a positive way, while governance can influence firm value in a negative way. Even though dividends and audit quality can influence firm value in a positive way, audit quality still cannot increase the influence of dividends on firm value. Audit quality also cannot increase the influence of ESG on dividends. In this case, inefficient ESG practices followed by poor audit quality are the main factor of this insignificant influence. It takes time for ESG investments to influence company performance, which has an impact on high dividend payout ratios and firm value.